Development of Application Score Sheet Traditional Sport Hadang on Information Technology - Irfanny, M; Soegiyanto, Soegiyanto; Sulaiman, Sulaiman (Journal of Physical Education and Sports, 2021)
The development of sports technology is increasingly sophisticated and modern in improving the quality of sports. Folk games or traditional sports are cultural assets that need to be preserved, because they have the potential to be further developed as sports that help improve physical quality for the players. The results of the validation of the first stage I referee experts were 62%, stage II 96%, stage I referee experts 66%, stage II 96% and IT experts I stage I 64%, stage II 94%, IT experts II stage I 60%, stage II 94%. The results of the small-scale questionnaire of the coaches were 66% in good category, 50% for enough category and 65% for scorer in good category. The results of the large-scale questionnaire of coaches were 95% very good category, 89% very good category players and 93% very good scorer categories. The conclusions of this study: (1) The product design development of application score sheet traditional sports of Hadang is the application of the traditional sports score sheet based on information technology. (2) The effectiveness of the product development of application score sheet traditional sports of Hadang, it can be said that it is effective as a score sheet application that helps the scorer in entering points, recording and saving match data. (3) The acceptance of the development of the application score sheet of traditional sport hadang based on information technology is said to be "Accepted" from the results of large-scale questionnaires with a percentage of 92.56%.